Analisis Nilai Pendidikan Karakter Disiplin dan Tanggung Jawab dalam Pembelajaran Musik Pada Pertunjukan CARITA di Sekolah Dasar - Agustri, Synta; Uswatun, Din Azwar; Nurmeta, Irna Khaleda (UNIVERSITAS MUHAMMADIYAH SURABAYA, 2025)
This study aims to analyze the values of character education, specifically discipline and responsibility, in music learning during the CARITA performance at SD Negeri Cicadas, Sukabumi. These two aspects are fundamental in shaping a good individual character, both in school and in society. The subjects of the study consisted of 5 male students: 1 student from grade 4, 3 students from grade 5, and 1 student from grade 6. The selection of upper-grade students was intended to make it easier for them to understand abstract values such as harmony, tempo, and dynamics in playing the gamelan, and the music curriculum aligns with the teaching materials. The study used a descriptive qualitative method with a phenomenological approach, involving the collection of primary data through observation, interviews, and documentation, as well as secondary data from references such as journals. Data analysis used the Miles and Huberman model, consisting of data reduction, data presentation, and conclusion drawing. The results of the study indicate that in the music learning process for the CARITA performance, the values of discipline and responsibility were evident in the students, both during the activities and the actual performance.